No association of risk variants for diabetes and obesity with breast cancer: the Multiethnic Cohort and PAGE studies - Chen, Fang (2011)
Body mass index is an established risk factor for post-menopausal breast cancer. Epidemiologic studies have also reported a positive association between type 2 diabetes (T2D) and breast cancer risk. To investigate a genetic basis linking these common phenotypes with breast cancer, we tested 31 common variants for T2D and obesity in a case-control study of 1,915 breast cancer cases and 2,884 controls nested within the Multiethnic Cohort (MEC) study. Following adjustment for multiple tests, we found no significant association between any variant and breast cancer risk. Summary scores comprised of the numbers of risk alleles for T2D and/or obesity were also not found to be significantly associated with breast cancer risk.